Evaluation of the effectiveness of renaturalization tools of renaturalized sections of Lithuanian rivers - Litvinaitis, Andrius; Kontautas, Antanas; Skersonas, Andrius; Ivanauskas, Edgaras; Bagdžiūnaitė-Litvinaitienė, Lina; Butkuvienė, Jurgita (International Conference “Environmental Engineering”, 2023)
More than 40% of natural riverbeds of Lithuanian rivers have been affected by straightening, in the installation of melioration systems. The solution of gentle renaturalization was chosen and mild renaturalization measures were installed in straightened sections of riverbeds. A detailed assessment of the ecological condition of the renaturalized river sections was carried out according to the physico-chemical, ecological condition, biological (fish index, river macroinverte-brates, river macrophyte indexes) quality elements at 2019–2022. The results of complex studies show the renaturalization measures implemented have the greatest positive effect on the studied parameters in the river with the strongest turbulent flow formed.